The Age, Education, and Occupation Characteristics is not Associated with Human Immunodeficiency Virus (HIV) Infection in Pregnant Mothers - Kade Y. Saspriyana; Â Ketut Suwiyoga; I Made Darmayasa (Indonesian Socety of Obstetrics and Gynecology, 2014)
Abstract Objective: To know the relation ship between age, education and occupation on the pregnant women and the HIVstatus of the husband against the risk of being infected with HIV. Method: This was an unpaired case cont rol study perform ed in the Obstetrics and Gynecology Department of Sanglah Hospital, Denpasar, from October to November 2011. The subjects were pregnant women who were willing to particip ate in the research, which were grouped into HIV-infected case and control group. Diagnosis of HIV was based on rapid test The data was analyzed using ChiSquar e test with the help of SPSS version 17.0 Result: There was fifty subjects consisting of 25 subjects in the case group and 25 subjects in contr ol group we obtained that the risk of HIV-infected pregnant women in the old vs young age, low vs higher education, and occupations at risk vs not at risk is not significant in the two groups. Each Odds ratio is 0.35 (CI =95% 0.08-1.55; P = 0.16),0.85 (CI=95% 0.28-2.59; P =0.77), and 2.09 (CI=95% 0.1824.62; P =1.00). Meanwhile, the odds ratio of the husband HIV status was 12.67 (CI =95% 3.31-48.50; P =0.01). Conclusion: Husband s infected with HIVincreases the risk of HIV in pregnant women 12 times greater than if the husband was not infected with HIV. Wher eas, age, education, and th e occupation of mothers is not a risk factor for the occurrence of HIV infection in pregnant women. Keywords: age, education, husband HIV statu s, occupation and pregnant women infected with HIV.